Prevalence of Hypoalbuminemia Among Older Adults Admitted with Intertrochanteric Fracture & Its Impact on Clinical Outcome (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Intertrochanteric fractures in older adults are associated with high morbidity and mortality. Nutritional status, particularly serum albumin level, is an important indicator of both nutritional reserve and overall systemic health. Aim & Objectives: To determine the prevalence of hypoalbuminemia among elderly patients with intertrochanteric fractures and to evaluate its association with clinical outcomes. Materials & Methods: A hospital-based cross-sectional observational study was conducted on 120 patients aged ≥60 years with radiologically confirmed intertrochanteric fractures. Serum albumin levels were measured within 24 hours of admission. Hypoalbuminemia was defined as serum albumin ≤3.5 g/dL. Nutritional status was assessed using the Mini Nutritional Assessment (MNA) score. Clinical outcomes included functional recovery, in-hospital mortality, and duration of hospital stay. Results: Hypoalbuminemia was observed in 73.3% of patients. It showed a significant association with poor functional outcomes and prolonged hospital stay (p < 0.05). However, no significant association was found between hypoalbuminemia and mortality. Additionally, MNA scores did not show a significant correlation with serum albumin levels. Conclusion: Hypoalbuminemia is highly prevalent among elderly patients with intertrochanteric fractures and serves as an important predictor of poor functional recovery and increased hospital stay. Early identification and nutritional intervention may help improve clinical outcomes in this high-risk population.